THEORETICAL FOUNDATIONS OF ECO-AESTHETIC COMPETENCE AND ITS FORMATION IN PRIMARY SCHOOL STUDENTS - Zokirova Sohiba Muxtoraliyevna; Alijonova Maftuna Maxamadjon qizi (Modern American Journals, 2025)
This article aims to thoroughly explore the theoretical foundations of eco-aesthetics, its origins, relevance, and conceptual meaning. It discusses the similarities and differences between eco-aesthetics and environmental education. The historical emergence and current roles of eco-aesthetics are outlined, along with several methods and recommendations for developing eco-aesthetic competence in primary school students.
Keywords: aesthetics, philosophy, ecology, nature, artificial beauty.